Impact of effective dose to immune cells (EDIC) on lymphocyte nadir and survival in limited-stage SCLC. (September 2021) - Yu, Yishan; Fu, Pingfu; Jin, Jian-Yue; Gao, Siming; Wang, Weili; Machtay, Mitchell; Wang, Linlin; Kong, Feng-Ming (Spring); Yu, Jinming
Highlights: EDIC significantly correlated with lymphocyte nadir during thoracic radiotherapy. Lymphocyte nadir and EDIC were independent factors for survival outcome in LS-SCLC. EDIC appear to have a better survival prediction accuracy than lymphocyte nadir. More attention should be paid to EDIC to avoid circulating lymphocyte toxicity. Abstract: Background: Effective dose to immune cell (EDIC), an estimated radiation dose to the circulating lymphocytes, is of significance for overall survival (OS) in non-small cell lung cancer. This study aimed to validate the EDIC's OS effect on limited-stage small cell lung cancer (LS-SCLC). Method and materials: This study included LS-SCLC patients received definitive chemo-radiation in one single center from 2012 to 2017. All patients had multiple complete-blood-count tests including lymphocyte count at pre-, during- and end- radiotherapy. EDIC, computed according to doses of the lung, heart, and the total body, was assessed for its correlation with lymphocyte nadir, OS and progression free survival (PFS). Results: Of 503 eligible patients, the mean EDIC was 7.34 Gy. The mean lymphocyte nadir was 0.48 × 10 9 cells/L, significantly lower than 1.65 × 10 9 cells/L at pre-radiotherapy ( p < 0.001). EDIC was significantly correlated with lymphocyte nadir under both univariate ( p < 0.001) and multivariable linear regression ( p < 0.001). Multivariable analysis showed EDIC (HR = 0.1072, p = 0.005) and lymphocyte nadir (HR = 0.345, p = 0.003) were both significant for OS. EDIC was also significant for PFS (HR = 1.046, p = 0.026). The C-indexes of OS prediction were 0.593, 0.617, 0.676, and 0.684, for lymphocyte nadir alone, EDIC alone, combined lymphocyte nadir model, and combined EDIC model, respectively. Conclusions: This study demonstrated that EDIC is an independent predictor for lymphocyte nadir, PFS and OS. EDIC may serve as a predictor for lymphocyte nadir and a surrogate marker for OS in LS-SCLC. More attention should be paid to EDIC to decease the lymphocyte toxicity and improve survival.